Cardiovascular and ventilatory interactions in the facultative air-breathing teleost Pangasianodon hypophthalmus - Armelin, Vinicius Araújo [UNESP]; Thomsen, Mikkel Thy; Teixeira, Mariana Teodoro [UNESP]; Florindo, Luiz Henrique [UNESP]; Bayley, Mark; Wang, Tobias (Springer Nature, 2019)
All vertebrates possess baroreceptors monitoring arterial blood pressure and eliciting reflexive changes in vascular resistance and heart rate in response to blood pressure perturbations imposed by, e.g., exercise, hypoxia, or hemorrhage. There is considerable variation in the magnitude of the baroreflex amongst vertebrate groups, making phylogenetic trends and association with major evolutionary events such as air-breathing and endothermy, difficult to identify. In the present study, we quantified the baroreflex in the facultative air-breathing catfish Pangasianodon hypophthalmus. Using a pharmacological approach, we quantified the cardiac limb of the baroreflex and by subjecting fish to hypoxia and by stimulation with NaCN with and without pharmacological autonomic blockade; we also examined the cardiovascular regulation associated with air-breathing. As in most other air-breathing fish, air-breathing elicited a substantial tachycardia. This tachycardia was abolished by cholinergic muscarinic pharmacological blockade, which also abolished the cardiac limb of the baroreflex, and consequently such fish failed to maintain their arterial blood pressure when air-breathing. In higher vertebrate classes, baroreceptors elicit ventilatory changes; however, whether this is the case in fish has not previously been investigated. Pangasianodon hypophthalmus demonstrated a prominent increase in ventilation during imposed hypotension. Collectively, these results demonstrate, for the first time, an efficient baroreflex in an air-breathing fish, point towards involvement of baroreceptors in blood pressure regulation during air-breathing, and show a correlation between blood pressure and ventilation, providing additional information on the origin of this link.
Keywords: Baroreceptors; Blood pressure regulation; Hypoxia; Pharmacology